The Logic of Re-Intermediation: An Introduction (Cinéma & Cie. Film and Media Studies Journal, 2017)
This special issue of Cinéma & Cie analyses the logic and processes of re- intermediation emerging in the contemporary European media industry landscape, providing an opportunity to bring questions of availability, text circulation and gatekeeping to the centre of scholarly debates and investigations. Through contributions showcasing a wide array of methodological and theoretical approaches, the volume illustrates and analyses the presence of new gatekeepers, their impact in shaping texts and their consumption in different European contexts. Its case studies include le sharing, Curzon Home Cinema, VOD services and the problematic implementation of the Digital Single Market policy.The introduction is structured in three parts. In the rst, we de ne the logic of re- intermediation as the change in traditional intermediaries and the development of new, different gatekeepers; we then emphasize its importance for a full understanding of the cultural and economic struggles in the contemporary European audiovisual market. The second part provides an example of the ongoing re-intermediation processes by focusing on the lesser known case of ‘aggregators’ for VOD platforms, in reference to the activities of the international company Under the Milky Way. Finally, the third part provides a detailed overview of the articles included in the special issue.